Clonal Propagation of Valeriana jatamansi Retains the Essential Oil Profile of Mother Plants: An Approach Toward Generating Homogenous Grade of Essential Oil for Industrial Use - Gautam, Rahul Dev; Kumar, Ajay; Kumar, Ravi; Chauhan, Ramesh; Singh, Satbeer; Kumar, Manish; Kumar, Dinesh; Kumar, Ashok; Singh, Sanatsujat (Frontiers in Plant Science, 2021)
Valeriana jatamansi Jones (Syn. V. wallichii DC.) is an aromatic, medicinal herb used as a tranquilizer and in treating sleep disorders. Rhizome is mainly used to extract essential oil and valepotriates. High quality and economic yield of rhizomes are available in the third year of growth. Therefore, the cultivation of Valeriana jatamansi is not picking up, and over-exploitation of this plant from wild habitats to meet the increasing demand of the pharmaceutical industry is the cause of threat to the genetic diversity of the species. Further, collections from the wild are heterogeneous, resulting in variable produce. The development of clonal lines can ensure uniform quality and yield of rhizome biomass. An effective clonal propagation method was standardized using different hormonal concentrations of naphthalene acetic acid (NAA) on apical shoot cuttings from the selected clone CSIR-IHBT-VJ-05 for different time durations and raised over various planting media. NAA treatment of 50 ppm concentration for 30 minutes was found optimum for root induction in apical shoots of Valeriana jatamansi. Variations for essential oil composition within the clone were non-significant, while samples of the control population were variable. The best quality essential oil (patchouli alcohol ~62%) was available during the third year of plant growth. A propagation technique for large-scale quality plant material (QPM) production has been standardized to reduce the stress over natural resources and promote Valeriana jatamansi for use in the aromatic and pharmaceutical industry.